Protocolos analgésicos no pós-operatório de cães com doença do disco intervertebral (hansen tipo i) submetidos à hemilaminectomia - Ferrarin, Dênis Antonio (2018)
In dogs with intervertebral disc disease (IVDD), surgical decompression procedures such as hemilaminectomy may be indicated depending on the severity of the neurological dysfunction. Surgery may induce intense and painful stimuli, and the postoperative analgesia is important for adequate patient recovery. This study was based on the scarcity of scientific literature addressing prospective postoperative pain assessments studies of spinal surgery in dogs, as well as the lack of consensus among authors on which analgesic protocol to adopt. Therefore, the aim of this study was to evaluate the postoperative analgesia of dogs presenting thoracolumbar or lumbar IVDD, submitted to hemilamectomy and different analgesic protocols. Sixteen dogs, randomly assigned into four groups according to the pre-determined postoperative analgesic protocol, underwent decompression surgery by dorsolateral hemilaminectomy. The group I (G1) protocol was composed by methadone, meloxicam and dipyrone; group II (G2) by methadone, meloxicam, dipyrone, and transcutaneous electrical nerve stimulation (TENS) acupuncture like, group III (G3) by meloxicam, dipyrone and TENS acupuncture like, and group IV (G4) only by meloxicam and dipyrone. All patients were blinded evaluated for pain, by two veterinarians, based on the visual analogue scale (VAS) and the short form Glasgow pain scale. The animals were assessed every 2 hours until 24 hours post-surgery and every 4 hours for another 24 hours, totalling 48 hours of evaluation. There was no statistical difference among groups regarding pain scores in both scales, demonstrating that the four protocols promoted analgesia. There were rescues in only two patients of the G1 and G2 groups. The four analgesic protocols consisting of methadone, dipyrone, meloxicam and TENS acupuncture like promoted analgesia in the initial 48 hours postoperatively in dogs with IVDD (Hansen type I) submitted to hemilaminectomy, allowing the clinician to choose one according to availability, clinical situation and reaction to side effects when opioids are present.